Blood-brain barrier disruption and hemorrhagic transformation in acute stroke before endovascular reperfusion therapy - Liang, Yuchen; Yu, Yang; Liu, Jiaxin; Li, Xuewei; Chen, Xue; Zhou, Hongwei; Guo, Zhen-Ni (Frontiers in Neurology, 2024)
Background and purpose Early blood–brain barrier (BBB) disruption in patients with acute ischemic stroke (AIS) can be detected on perfusion computed tomography (PCT) images before undergoing reperfusion therapy. In this study, we aimed to determine whether early disruption of the BBB predicts intracranial hemorrhage transformation (HT) in patients with AIS undergoing endovascular therapy and further identify factors influencing BBB disruption. Methods We retrospectively analyzed general clinical and imaging data derived from 159 consecutive patients with acute anterior circulation stroke who were admitted to the Department of Neurology of the First Hospital of Jilin University, and who underwent endovascular treatment between January 1, 2021, and March 31, 2023. We evaluated the relationship between BBB destruction and intracranial HT before endovascular reperfusion therapy and examined the risk factors for early BBB destruction. Results A total of 159 patients with assessable BBB leakage were included. The median (interquartile range, IQR) age was 63 (54–70) years, 108 (67.9%) patients were male, and the median baseline National Institutes of Health Stroke Scale (NHISS) score was 12 (10–15). Follow-up non-contrast computed tomography (NCCT) detected HT in 63 patients. After logistic regression modeling adjustment, we found that BBB leakage in the true leakage area was slightly more than 2-fold risk of HT (odds ratio [OR], 2.01; 95% confidence interval [CI] 1.02–3.92). Heart rate was also associated with HT (OR, 1.03, 95% CI, 1.00–1.05). High Blood–brain barrier permeability (BBBP) in the true leakage area was positively correlated with infarct core volume (OR, 1.03; 95% CI, 1.01–1.05). Conclusion Early BBB destruction before endovascular reperfusion therapy was associated with HT, whereas high BBBP correlated positively with infarct core volume.